Detektory výkonu jaderného reaktoru založené na měření jasu Čerenkovova záření - Čejka, Lukáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2015)
Tato práce řeší vztah mezi jasem Čerenkovova záření v jaderném reaktoru a výkonem jaderného reaktoru. Čerenkovovo záření vzniká při průchodu nabitých částic hmotným prostředím, pokud je jejich rychlost vyšší než fázová rychlost světla v daném prostředí. V jaderných reaktorech moderovaných vodou vzniká díky vytržení elektronů z obalů působením gama záření. Měření je provedeno pomocí fotoaparátu a softwaru na fotometrické měření jasu. Dále je zde řešeno využití detekce Čerenkovova záření pro měření vyhoření použitého jaderného paliva. Jsou zde uvedeny příklady využití detekce Čerenkovova záření pro měření výkonu jaderných reaktorů, včetně analýzy naměřených výsledků na školním jaderném reaktoru VR-1. Naměřené výsledky ukazují, že při rostoucím výkonu roste i intenzita Čerenkovova záření, ovšem při prudkém snížení se objevuje zbytkové záření způsobené zpožděným gama zářením. Možné využití detekce jasu Čerenkovova záření je při monitorování nepředvídatelného zvýšení výkonu reaktoru či při kontrole použitého paliva.

This work deals with the connection between the luminance of Cherenkov radiation in a nuclear reactor and his power. Cherenkov radiation arises when charged particle passing through the medium if their speed is higher than the phase velocity of light in that medium. In water moderated reactors, it is caused by secondary electrons produced by absorption of gamma rays. The measurement is done using the camera and software for photometric luminance measurements. Furthermore, there is mentioned the use of Cerenkov radiation detection to measure burnout of spent nuclear fuel. There are examples of usage of Cherenkov radiation detection to measure of nuclear reactors power, including an analysis of the measured results on research nuclear reactor VR -1. The measured results show increasing intensity of Cherenkov radiation with increasing reactor power, but residual detection response caused by delayed gamma radiation was observed after the rapid decrease of the reactor power. Possible use of detection luminance of Cherenkov radiation is in monitoring unforeseen increase in reactor power or in the control of used fuel.
Nuclear reactor power detectors based on Cherenkov radiation measurement
Keywords: Čerenkovovo záření; výkon reaktoru; jaderné palivo; Cherenkov radiation; reactor power; nuclear fuel